Enablers and barriers to the successful implementation of project control systems in the petroleum and chemical industry. (4th January 2018) - Jawad, Sahar; Ledwith, Ann; Panahifar, Farhad
Project budget and schedule overruns are becoming critical challenges within the petroleum and chemical industry due to a sharp decline in the oil prices and the subsequent impact this has had on the global financial market. Although innovative project control systems (PCSs) are typically employed in this sector, experience reveals that such systems do not guarantee project success unless they are effectively implemented. The effective implementation of such systems should show financial governance and control, improved profit and financial forecasting, and the ability to forecast and mitigate negative cost impact. This study aims to identify, examine, and prioritize the enablers and barriers linked with successful implementation of PCS. A multicriteria model was used to collect, evaluate, and analyze data from petroleum and chemical firms in Saudi Arabia. A total of 9 enablers and 15 barriers were identified. The research revealed that skilled project team members and clear definition of roles and responsibilities are key enablers of successful PCS. The most critical barriers identified by this study were poor skills in scheduling and controlling along with a distrust of the control system. Other barriers identified include disparate control systems between owner and contractor and vague contract deliverables. These findings emphasize the need to (1) build a project team with the right skills and clear roles, (2) develop a control system that is accurate and trusted by the project team, and (3) develop a shared understanding between owner and contractor about the control system and contract deliverables, in order to successfully implement PCS.